2016
DOI: 10.1038/srep20179
|View full text |Cite
|
Sign up to set email alerts
|

SMARCAD1 is an ATP-dependent stimulator of nucleosomal H2A acetylation via CBP, resulting in transcriptional regulation

Abstract: Histone acetylation plays a pivotal role in transcriptional regulation, and ATP-dependent nucleosome remodeling activity is required for optimal transcription from chromatin. While these two activities have been well characterized, how they are coordinated remains to be determined. We discovered ATP-dependent histone H2A acetylation activity in Drosophila nuclear extracts. This activity was column purified and demonstrated to be composed of the enzymatic activities of CREB-binding protein (CBP) and SMARCAD1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Depletion of this enzyme results in an open chromatin conformation in normally transcriptionally repressed regions and can affect gene expression, suggesting that SMARCAD1 ensures correct chromatin structure of silent domains. SMARCAD1 can also activate transcription together with co-activator p300/CBP (CREB-binding protein), and interactions with the transcription machinery have recently been reported in S. pombe (20,21). In addition, SMARCAD1 is involved in double-strand break repair (22).…”
Section: Chromatin In Embryonic Stem Cells (Escs) Differs Markedly Frmentioning
confidence: 99%
“…Depletion of this enzyme results in an open chromatin conformation in normally transcriptionally repressed regions and can affect gene expression, suggesting that SMARCAD1 ensures correct chromatin structure of silent domains. SMARCAD1 can also activate transcription together with co-activator p300/CBP (CREB-binding protein), and interactions with the transcription machinery have recently been reported in S. pombe (20,21). In addition, SMARCAD1 is involved in double-strand break repair (22).…”
Section: Chromatin In Embryonic Stem Cells (Escs) Differs Markedly Frmentioning
confidence: 99%
“…The Smarcad1/Etl1/Fun30 family of chromatin remodeling factors is one of the most highly conserved families, found from fission (Fft1-3) and budding yeast (Fun30) to mouse (Smarcad1) and human (SMARCAD1), and is defined by the presence of CUE-domains in addition to the helicase-like domains [5]. Smarcad1 and its homologs have roles in gene regulation including gene silencing [5][6][7][8][9], heterochromatin maintenance [10,11], genome organization [12,13], and DNA repair [14,15]. A mutation in a skin-specific isoform of SMARCAD1 in humans causes adermatoglyphia (the loss of finger prints) and Basan syndrome, which affects skin integrity [16][17][18].…”
mentioning
confidence: 99%
“…It was shown that the Fun30 (function unknown now 30) protein, which is a member of Swi2/Snf2 (switch/sucrose non-fermentable) family of proteins involved in chromatin remodeling, can facilitate the action of DNA2 in end resection by overcoming inhibiting effects induced by Rad9, which otherwise create a barrier for the resection [ 92 ]. The potential human homologue of Fun30 is already presented SMARCAD1, which was shown to be involved in end resection and colocalize with DSB repair markers, including γH2AX [ 73 , 93 ].…”
Section: Dna Damage Responsementioning
confidence: 99%